Body Image and its Relation with Coping Strategies in Breast Cancer Patients: A Descriptive Study in Sulaimaniyah, Iraq - Sharif, Bakhan Farah Hama; Saeed, Mahabat Hassan; Nouri, Bijan; Valiee, Sina (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: Breast cancer is several of the worst severe illnesses for women, which influences their physical and mental quality of life and acceptance of their bodies. It affects patients' views of their bodies; thus, finding effective coping mechanisms is essential. Objective: This study aimed to discover body image and its relation with coping mechanisms in breast cancer patients admitted to Hiwa Hematology/Oncology Hospital in Sulaimaniyah, Iraq. Materials & Methods: This Cross-sectional study was conducted on women diagnosed with breast cancer admitted to the Hiwa Hematology/Oncology Hospital Sulaimaniyah, Iraq. A three-part questionnaire was utilized to gather information to determine body image and coping mechanisms that were demographic and clinical form, body image scale and Coping Orientation to coping or regulating cognitions in response to stressors (Brief-COPE). Results: The mean score for the body image was reported as 7.86±7.73, the mean score for coping strategies, including problem-focused /active coping strategies items was reported as 2.74±0.67, and functional items as 2.82±0.43. Considering the calculated mean scores, the distress or concerns of the participants about their body image were lower. The most frequent coping strategies were religious coping (3.88±0.32), while the least active coping approach was humor (1.96±1.08). Self-distraction (3.13±1.03) was the least avoidant coping strategy. A significant positive relationship between the coping strategies with body image was reported as (p=0.032, r=0.200). Conclusions: Good body image in women was associated with increased usage of practical acceptance. Therefore, it is advised to promote a positive view of physical appearance and having skilled nurses assess all breast cancer patients' capacity for coping following surgery. Nurses and patients can effectively communicate about body image and coping techniques through these assessments.
Keywords: Breast cancer; body image; coping strategies; Iraq